Enhancing Fine Motor Skills in Children with Mental Disabilities through Basic Lego-Based Interventions - Mandich, IJzendoorn; Rubin, Berloffa (Institute for Law and Economics Studies, 2023)
This research investigates the efficacy of utilizing basic Legos to enhance the fine motor skills of children diagnosed with various mental disabilities. The study explores the impact of structured activities involving basic Legos on the development of fine motor skills in this specific demographic. A mixed-methods approach was employed, incorporating both quantitative assessments and qualitative insights. Quantitative evaluations using standardized measures, such as the Peabody Developmental Motor Scales (PDMS) and the Bruininks-Oseretsky Test of Motor Proficiency (BOT-2), demonstrated statistically significant improvements in fine motor skills post-intervention. Qualitative data obtained through observations and interviews echoed these quantitative findings, indicating increased engagement, improved problem-solving abilities, and heightened emotional involvement among the children during Lego-based activities. The findings suggest a positive impact of engaging children with mental disabilities in activities involving basic Legos. These results offer potential implications for therapeutic interventions, educational strategies, and the overall quality of life for this demographic. The outcomes contribute to a better understanding of effective and engaging interventions, stimulating further research and practical applications that support the growth and well-being of these children.